Association Between Type of Health Professional at Birth and Exclusive Breastfeeding. (20th September 2017) - Haile, Zelalem T.; Elmasry, Mohamed; Chavan, Bhakti; Azulay Chertok, Ilana R.
Abstract : Introduction: Although benefits of breastfeeding for infants, women, and society are well established, breastfeeding rates in the United States remain below the Healthy People 2020 goals. Various factors are known to influence breastfeeding practices. Limited research has been conducted to examine the influence of type of birth attendant on exclusive breastfeeding. Methods: A cross‐sectional analysis was conducted using data from the Infant Feeding Practices Study II collected between May 2005 and June 2007. Results: The study sample included 2026 women, aged 18 years or older. At discharge, 74.6% of women exclusively breastfed, and 27.6% exclusively breastfed at 3 months postpartum. Bivariate analysis showed a statistically significant association between type of health professional at birth and exclusive breastfeeding at discharge ( P = .001) and 3 months postpartum ( P < .001). After adjusting for potential confounders, the association between type of health professional at birth and exclusive breastfeeding at discharge was no longer significant. However, the odds of exclusive breastfeeding at 3 months postpartum were higher among women whose birth was attended by a midwife or nurse‐midwife compared to those whose birth was attended by an obstetrician (odds ratio [OR], 1.87; 95% confidence interval [CI], 1.34‐2.61; P < .001). Discussion: Exclusive breastfeeding continuation may be influenced by the type of health professional attending the birth. In addition to having a skilled workforce, health care professionals involved in perinatal care need to be educated and trained to promote and support exclusive breastfeeding as recommended. The complex and multifactorial nature of the maternal decision to exclusively breastfeed requires broader understanding of contextual factors.